2021
DOI: 10.1002/dc.24875
|View full text |Cite
|
Sign up to set email alerts
|

Pleomorphic liposarcoma with liver metastasis diagnosed by combined fine‐needle aspiration cytology and core‐needle biopsy

Abstract: Pleomorphic liposarcoma (PLPS) is the rarest liposarcoma subtype, with high-local recurrence and metastasis rates. Fine-needle aspiration cytology (FNAC) is successfully used in the diagnosis of primary or metastatic soft tissue tumors, but liver metastases of PLPS diagnosed by FNAC have never been reported. The cytological diagnosis depends on the identification of lipoblasts with sharply defined cytoplasmic vacuoles indenting and distorting the nucleus in the context of a pleomorphic tumor and in a proper cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Therefore, special attention is required in such cases, as differential diagnosis may be necessary [ 66 ]. Ciliberti et al reported the case of a 51-year-old man with a history of lung carcinoma who developed a pleomorphic liposarcoma of the shoulder girdle deep soft tissue and acquired hepatic metastases [ 67 ]. Considering the patient’s medical history, lung carcinoma metastasis was first taken into consideration, but a histopathological examination of the specimen revealed the presence of giant multinucleated lipoblasts with multivacuolated cytoplasm [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, special attention is required in such cases, as differential diagnosis may be necessary [ 66 ]. Ciliberti et al reported the case of a 51-year-old man with a history of lung carcinoma who developed a pleomorphic liposarcoma of the shoulder girdle deep soft tissue and acquired hepatic metastases [ 67 ]. Considering the patient’s medical history, lung carcinoma metastasis was first taken into consideration, but a histopathological examination of the specimen revealed the presence of giant multinucleated lipoblasts with multivacuolated cytoplasm [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ciliberti et al reported the case of a 51-year-old man with a history of lung carcinoma who developed a pleomorphic liposarcoma of the shoulder girdle deep soft tissue and acquired hepatic metastases [ 67 ]. Considering the patient’s medical history, lung carcinoma metastasis was first taken into consideration, but a histopathological examination of the specimen revealed the presence of giant multinucleated lipoblasts with multivacuolated cytoplasm [ 67 ]. Immunohistochemical analysis revealed the expression of vimentin within the tumor cells, while MDM2 and Hep-Par1 were negative [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, LN-FNAC and LN-CNB may represent the right solution. Unfortunately, LN-FNAC is not universally accepted as a diagnostic tool whereas it has been useful in evaluating malignant processes in cases in which surgical excisions were difficult to perform [25,28,82,83,[88][89][90][91][92][93][94]. Moreover, LN-FNAC has been useful in the management of oncological patients, through the possibility of selecting patients who will truly benefit from CNB and, eventually, surgical excision.…”
Section: Pathology Of Covid-19 Post-vaccine Lymphadenopathymentioning
confidence: 99%
“…[5][6][7][8][9] Other FNA studies have fewer cases, are single case reports, or are examples of PLPS merely being listed as part of a larger group (or groups) in Cancer Cytopathology September 2022 discussions of the cytology of various sarcomas. [10][11][12][13][14][15][16][17][18][19][20] Thus, we undertook a review of our combined FNA biopsy experience with 20 patients with PLPS.…”
Section: Introductionmentioning
confidence: 99%
“…Reporting the cytopathology of PLPS has been the specific subject of 5 publications having 5 or more patients (5‐13 cases) 5‐9 . Other FNA studies have fewer cases, are single case reports, or are examples of PLPS merely being listed as part of a larger group (or groups) in discussions of the cytology of various sarcomas 10‐20 . Thus, we undertook a review of our combined FNA biopsy experience with 20 patients with PLPS.…”
Section: Introductionmentioning
confidence: 99%